The Impact of Plastic Pollution on Terrestrial Ecosystems: Microplastics, Heavy Metals, and Quorum Sensing in Soil Health - Lalit Kumar (International Journal of Environmental Noise and Pollution Control, 2024)
Plastic pollution is one of the most significant environmental challenges today, particularly in the context of terrestrial ecosystems. The widespread accumulation of plastic waste, including microplastics, has led to pervasive contamination of soil, disrupting ecosystems and human health. This article explores the interactions between plastic pollutants and the terrestrial environment, with a focus on soil pollution, microplastic behavior, and the implications for ecosystems. Microplastics, which are tiny plastic particles with a diameter of less than 5 mm, have been observed in soil all over the world and interact with wildlife & soil microbes. These interactions can lead to the bioaccumulation of heavy metals, which are often adsorbed onto plastic particles, thus exacerbating environmental toxicity. The presence of plastic waste in soils can also interfere with natural processes like quorum sensing, which is essential for microbial communication and immune modulation within ecosystems. Disrupting these microbial behaviors can result in altered soil health, impacting nutrient cycling, plant growth, and overall ecosystem stability. This review further discusses the immunomodulatory effects of plastic-induced pollution, which alter organismal defense mechanisms, and the broader chemical effects on microbial and plant communities. Through examining these interactions, the article aims to raise awareness of the complex impacts of plastic pollution and suggests potential remedies for mitigating its harmful effects on the environment.
Keywords: Heavy metals; Microplastics; Plastic pollution; Quorum sensing; Soil Pollution